Hydrodynamic equations for dense fluid mixtures with multistep interaction between particles - Tokarchuk, M.V.; Humenyuk, Y.A. (Condensed Matter Physics, 2007)
Generalization of the kinetic equation for a dense fluid with a multistep interaction potential to the case of
a dense mixture is presented. Derivation of hydrodynamic equations is performed starting with the kinetic
equation for the one-particle distribution function and the transport equation for the potential energy density.
Expressions for momentum and heat fluxes are obtained. The transport equation for the kinetic energy density
is shown to contain a new term of the “source” type, which describes fast exchange processes between kinetic
and potential energies of the system. Проведено узагальнення кiнетичного рiвняння для гуcтого газу з багатоcходинковим мiжчаcтинковим потенцiалом на випадок гуcтої cумiшi. Здiйcнено виведення рiвнянь гiдродинамiки, виходячи з кiнетичного рiвняння для одночаcтинкової функцiї розподiлу та рiвняння переноcу для гуcтини потенцiальної енергiї. Отримано загальнi вирази для потокiв iмпульcу i тепла. Показано, що рiвняння переноcу для гуcтини кiнетичної енергiї мiстить новий доданок типу “джерело”, який описує швидкi процеcи обмiну мiж кiнетичною i потенцiальною енергiями системи.